2018
DOI: 10.3390/f9080452
|View full text |Cite
|
Sign up to set email alerts
|

The Red Palm Weevil in the City of Bari: A First Damage Assessment

Abstract: Phoenix canariensis Chabaud (Canary Palm) is one of the most distinctive landscape elements of several coastal urban centers in Italy. However, over the past few years, international trade has increased the risk of the introduction of Rhynchophorus ferrugineus (Red Palm Weevil) in the country, causing the death of numerous plants. In this work we assessed the damage caused by the insect to Canary Palm in the City of Bari, Apulia Region, furnishing useful information to decision makers and communities for prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…However, the pest number/damage proportionality allows using such proper techniques as pest trapping and similar approaches for thresholds evaluation [ 61 ]. In control actions, the damage forecast should promptly compare the damage value with the control cost [ 62 , 63 ]. The pest control issue consists of managing the pest population to get acceptable damage without suppressing all the pest individuals.…”
Section: Non-vector/vector Pest Damagementioning
confidence: 99%
See 1 more Smart Citation
“…However, the pest number/damage proportionality allows using such proper techniques as pest trapping and similar approaches for thresholds evaluation [ 61 ]. In control actions, the damage forecast should promptly compare the damage value with the control cost [ 62 , 63 ]. The pest control issue consists of managing the pest population to get acceptable damage without suppressing all the pest individuals.…”
Section: Non-vector/vector Pest Damagementioning
confidence: 99%
“…The need for a quantitative evaluation of the target population (Aphrophoridae, until now) exists because the control targets are the Aphrophoridae as vectors and not as conventionally damaging pests [ 130 ]. In the case of conventionally dangerous pest [ 62 , 210 , 211 ], even a non-quantitative pest population census method works because the need is to correlate the number of individuals (e.g., per trap) with an (economic/action) threshold. Such a correlation considers the damage rather than population census.…”
Section: Vector–pathogen: Rationale Controlmentioning
confidence: 99%
“…They concluded that incorporating human-assisted pathway predictors can greatly improve early detection of invasive species. Sardaro et al [2] conducted the first damage assessment of the effects of red palm weevil (Rhynchophorus ferrugineus Olivier) on Canary palm (Phoenix canariensis Chabaud), one of the most distinctive landscape elements in the City of Bari, Italy. The study offers important information for decision making and proper preservation measures for important urban green resources in urban settings.…”
Section: Contributions In Briefmentioning
confidence: 99%
“…Over the centuries landraces, based on traditional systems of production, ensured food and forage, minimized the production risk, stabilized yields [ 1 ], and favored low levels of technology and inputs [ 2 , 3 , 4 , 5 ]. Nowadays, landraces contribute to preserve social, cultural, health, recreational and identity values of community, so as to ensure wellbeing [ 6 ]. These benefits are mainly supplied in internal and marginal territories, i.e., rural areas characterized by scarce accessibility to main services, such as education, health and mobility.…”
Section: Introductionmentioning
confidence: 99%